Analysis Financial Kud Sentosa Village Air Terbit District Of East Tapung Sub-Province Of Kampar - Riyu Wardi Chandra Putra; Yusmini '; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This reseacrh is aimed to analyze the financial KUD Sentosa during last three years that evaluated from monetery ratio of KUD. This research was happened at KUD Sentosa village Air Terbit District Of East Tapung Sub- Province Of Kampar. The method that used was case study in order to see the monetary ratio of KUD Sentosa, The research result shown from monetery ratio by calculating the ratio of liquidity KUD reside in liquid position, ratio indicate that KUD Sentosa is in solvable reside. Active ratio shown that KUD Sentosa still depend from the using of foreign capital, if shown from rentability ratio advantage obtained by KUD is still lower compared with the using of total grand capital. Keywords: KUD of Sentosa, monetary ratio of KUD, solvable and likuid